Field Evaluation of Toltrazuril and Garlic for Treatment of Coccidiosis in Broiler Chickens - Kairy, Mohamed H.; Abd El Fadel, Hosney; Ad El Aleim, Abd El Aleim F.; Gad, Gehan N.; Abdel-Hamid, Fatma El Zahra (Journal of Advanced Veterinary Research, 2023)
This study was performed to investigate the effect of toltrazuril and fresh crushed garlic on the treatment of broiler chicks infected with coccidiosis. A hundred one-day old unsexed Cobb broiler chicks were used in this study. Chicks are classified into 5 equal groups (n=20 birds/group), Gp (1) contained 20 healthy broilers and acted as a negative control. Birds of groups 2, 3, 4, and 5 were inoculated orally with 1x105 sporulated oocysts of Eimeria tenella (E. tenella) (field isolate) on the 14th day of age. Group 2 was experimentally infected, did not receive treatment and acted as a positive control. Group 3 was experimentally infected and treated with toltrazuril (1ml/liter drinking water) for two successive days. Group 4 was experimentally infected and treated with fresh crushed garlic (50 g/Kg ration) for 5 successive days. Group 5 was experimentally infected and treated with toltrazuril (1ml/liter drinking water) and fresh crushed garlic (25g/Kg ration) for 5 successive days. All birds were individually weighed at the beginning of the experiment, 1st and 10th days post treatment. Five birds from each group were sacrificed and two blood samples from each chick were collected for determination of erythrogram, MDA and CAT. Specimens from intestine were collected for histopathological study. The obtained results showed that the broilers infected with E. tenella had loss of appetite, depression, ruffled feathers, debility, dropped head and bloody diarrhea. Infected chicks with coccidia induced a significant decrease in the body weight, weight gain, RBCs, Hb, PCV%, platelets, and MCHC. Beside, an increase in FCR, MCV, MCH, and MDA assoiated with non-significant decrease in CAT was recorded. Infected birds treated with toltrazuril and garlic either alone or in a combination could recover birds from the clinical signs. Moreover, we recorded a significant increase in body weight, weight gain coupled with non significant increase in RBCs, Hb and PCV%, Platelet, MCHC and non-significant decrease in MCV and MCH compared with experimentally infected and non treated group (+ve control). Infected broilers with coccidiosiss induced pathological lesions in the small intestine represented as ruptured villi, and diffused haemorrhage. Treatment of the infeted birds with toltrazuril and garlic showed apparently normal mucosa, submucosa and muscularis mucosa with serosa. It could be concluded that the infected broiler chickens with E. tenella induced adverse effects in body performance, erythrogram and pathological changes. Treatment of infected chicks with toltrazuril and garlic led to disappearance of the clinical signs, improved body performane and pathological effects.